The Impact of Rectal Stump Inflammation After Subtotal Colectomy on Pouch Outcomes in Ulcerative Colitis Patients - Wasmann, Karin A (J Crohns Colitis, 2020)
BACKGROUND AND AIMS: Proctitis after subtotal colectomy with ileostomy for ulcerative colitis [UC] is common, but its impact on short- and long-term outcome after pouch surgery is unknown. The aim of this study was to determine the incidence of proctitis after subtotal colectomy and its impact on postoperative morbidity and pouchitis. METHODS: The distal margin of the rectal stump of all consecutive patients undergoing completion proctectomy and pouch procedure for UC, between 1999 and 2017, was revised and scored for active inflammation according to the validated Geboes score, and for diversion proctitis. Pathological findings were correlated to complications after pouch surgery and pouchitis [including therapy-refractory] using multivariate analyses. RESULTS: Out of 204 included patients, 167 [82%] had active inflammation in the rectal stump and diversion colitis was found in 170 specimens [83%]. Overall postoperative complications and anastomotic leakage rates were not significantly different between patients with and without active inflammation in the rectal stump [34.7% vs 32.4%, p = 0.79, and 10.2% vs 5.4%, p = 0.54, respectively]. Active inflammation of the rectal stump was significantly associated with the development of pouchitis [54.3% vs 25.5%, plog = 0.02], as well as with therapy refractory pouchitis [14% vs 0%, plog = 0.05]. Following multivariate analysis, active inflammation was an independent predictor for the development of pouchitis. Diversion proctitis showed no association with these outcome parameters. CONCLUSIONS: Active inflammation in the rectal stump after subtotal colectomy occurs in 80% of UC patients and is a predictor for the development of pouchitis and therapy-refractory pouchitis.